2006
DOI: 10.1007/s10333-006-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of NO3-N in groundwater of the reservoir of the Sunagawa Subsurface Dam, Miyako Island, Japan

Abstract: The Japanese government started to construct two subsurface dams on Miyako Island in 1988, and the project was completed in 2001. Before the construction of the dams, the NO 3 -N concentration of groundwater on the island was about 10 mg/l, the upper limit for drinking water in Japan, owing to the application of fertilizer to sugarcane fields. Predicting the effect of these subsurface dams on the groundwater environment was difficult because they were probably the first mega-subsurface dams in the world. We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Good hydraulic connectivity and rapid groundwater movement caused by pumping facilitated nitrate transportation and equalized its distribution in the reservoir. A similar observation was documented in the study of the nitrate contamination of the Sunagawa artificial underground reservoir by Ishida, S. et al [36,37]. Due to pumping a large amount of groundwater for irrigation, an extensive uniform area of NO3-N concentration in the Sunagawa artificial underground reservoir was developed.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Good hydraulic connectivity and rapid groundwater movement caused by pumping facilitated nitrate transportation and equalized its distribution in the reservoir. A similar observation was documented in the study of the nitrate contamination of the Sunagawa artificial underground reservoir by Ishida, S. et al [36,37]. Due to pumping a large amount of groundwater for irrigation, an extensive uniform area of NO3-N concentration in the Sunagawa artificial underground reservoir was developed.…”
Section: Resultssupporting
confidence: 77%
“…Long-term monitoring of the nitrate concentration in the artificial underground reservoir of the Sunagawa subsurface dam before and after the dam’s construction indicated that the subsurface dam and pumping stored water greatly affected groundwater flow and water mixing in the reservoir area. The NO3-N concentration decreased gradually and harmonized with the decrease in cultivation acreage [36,37]. Yoshimoto, S. et al [38] proposed a numerical model consisting of a water balance sub-model and nitrogen balance sub-model to predict the long-term changes of groundwater nitrate in the reservoir area of the Komesu subsurface dam.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, first, the authors propose a remote online detection method to measure ground water quality parameters that are composed of chemical oxygen demand (COD) [20], total organic carbon (TOC) [21], nitrate nitrogen (NO 3 –N) [22], and turbidity (TURB) [23,24]. Section 2 describes the principle of UV spectrophotometry and the data processing methods in detail.…”
Section: Introductionmentioning
confidence: 99%
“…For example, numerous studies have reported extensive nitrate groundwater contamination in the Ryukyu limestone aquifer in the southern part of Okinawa Island, and most of these studies have concluded that chemical fertilizer is the major source of this nitrogen (e.g., Agata, Satake, & Tokuyama, 2001;Nakano, Yasumoto, Terasawa, & Nawa, 2013;Tokuyama, Yonaha, & Ohde, 1990;Yoshimoto, Tsuchihara, Ishida, & Imaizumi, 2007). In the unsaturated zone of the Ryukyu limestone aquifer on Miyako-jima Island in Okinawa Prefecture, the lag time for groundwater recharge from the ground surface (10 m) with fertilizer-derived nitrogen was estimated to be 7 years (Ishida, Tsuchihara, & Imaizumi, 2006;Tashiro & Takahira, 2001).…”
Section: Introductionmentioning
confidence: 99%